Establishing the rules of formation of fire-resistant biocomposites for building materials - Tsapko, Yuriy; Tsapko, Аleksii; Likhnyovskyi, Ruslan; Shumbar, Kostiantyn; Slutska, Oksana; Berdnyk, Oksana; Borysova, Anna; Dotsenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of forming a heat-insulating layer of foam coke under thermal action on a biocomposite with the presence of an intumescent coating. The task addressed is to establish the effectiveness of the formation of a heat-insulating intumescent layer of foam coke under thermal action on an intumescent coating, which effectively inhibits high temperature. It has been proven that when wood and fabric are treated with fire retardants, chemical bonds arise that characterize symmetric and asymmetric valence vibrations of C–H in the methyl and methylene groups of lignin and cellulose. For wood treated with an intumescent coating, the value of the adhesive strength was set at 0.25 MPa, while the destruction occurred along the polymer shell with a detachment area of about 25 %. For particleboard treated with an intumescent coating, the value of the adhesion strength is about 0.45 MPa, while the failure occurred along the polymer shell with a separation area of about 10 %. Based on the results, it was found that under the action of the burner flame, the temperature of the gaseous combustion products did not exceed 185 °C, and the mass loss was less than 2 %. During the thermal action of the coating, a layer of foam coke more than 20 mm thick was formed. Under the action of the burner flame on the biocomposite based on tarpaulin fabric, intensive swelling of the coating began, which led to the formation of a heat-insulating layer of foam coke more than 9 mm thick, ignition and flame spread did not occur. Thus, the mechanism of fire protection by an intumescent coating is determined by decomposition under the influence of temperature with heat absorption and release of non-combustible gases; by inhibiting oxidation in the gas and condensed phases and by forming a heat-protective coke layer on the surface of the material. The practical significance of the study is that the results related to determining the flame retardant properties of biocomposites could be taken into account when designing fire-resistant structures